Event-triggered H∞ filter design for Markovian jump systems with quantization. (May 2018) - Wang, Huijiao; Zhang, Dong; Lu, Renquan
Abstract: The problem of event-triggered H ∞ filter design for Markov jump systems with output quantization is investigated in this paper. A dynamic event-triggered communication scheme is introduced to detect whether or not transmit the newly sampled data to the quantizer for different jumping modes. Time interval analysis approach is used to unify the Markov jump system, the event-triggered scheme and network-induced delays into a new Markov jump filtering error system with time-delay. Based on reciprocally convex approach, conditions are derived to guarantee the networked Markov jump system mean-square stable with an H ∞ norm bound. The correspondent H ∞ filter and the event-triggered parameters are also co-designed. Two numerical examples are given to show the effectiveness and better performance of the proposed analysis and design techniques.